Biodegradation of Mineral and Silicone Plasters and Its Comparison. (June 2019) - Ryparová, P; Kostelecká, M; Tywoniak, J
Abstract: The article focuses on the determination of a fungal growth range on plaster depending on external conditions. The experiments compare three types of plaster which are the most widely used in Europe. The selected plaster is two mineral and one silicone. These types of plaster are standard mixtures developed and donated by manufacturing company from Czech Republic. The article contains comparison of germination and growth of mould on the surface of samples with the type of used degradation process before inoculation of mould. The types of used degradation were carbonation, freeze-thaw cycle, degradation by soil microorganism and high moisture. The microbial resistance was made based on modified Norm ČSN EN ISO 846. The samples were placed on mineral agar and in the 100 % humidity. The resistance of samples was evaluated by microscopy analyses.